2019
DOI: 10.1001/jamanetworkopen.2019.9020
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nonradioactive Multispectral Optoacoustic Tomographic Imaging With Conventional Lymphoscintigraphic Imaging for Sentinel Lymph Node Biopsy in Melanoma

Abstract: IMPORTANCE The metastatic status of sentinel lymph nodes (SLNs) is the most relevant prognostic factor in breast cancer, melanoma, and other tumors. The conventional standard to label SLNs is lymphoscintigraphy with technetium Tc 99m. A worldwide shortage and known disadvantages of Tc 99m have intensified efforts to establish alternative, nonradioactive imaging techniques. OBJECTIVE To assess a new nonradioactive method using multispectral optoacoustic tomographic (MSOT) imaging in comparison with conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 64 publications
(118 reference statements)
3
24
0
2
Order By: Relevance
“…The appropriate treatment for inguinal metastatic melanoma has gained increasing interest in recent years. Contemporary research with the use of multispectral optoacoustic tomographic imaging may allow the nonradioactive detection of sentinel lymph nodes and thereby eventually replace the SLNB [ 36 ]. Other recent developments in the treatment of inguinal metastatic melanoma concern adjuvant immunotherapy and molecular targeted therapy [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appropriate treatment for inguinal metastatic melanoma has gained increasing interest in recent years. Contemporary research with the use of multispectral optoacoustic tomographic imaging may allow the nonradioactive detection of sentinel lymph nodes and thereby eventually replace the SLNB [ 36 ]. Other recent developments in the treatment of inguinal metastatic melanoma concern adjuvant immunotherapy and molecular targeted therapy [ 37 , 38 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The concordance rate of ICG-labeled and technetium 99-marked detection of sentinel lymph node basins was 94.6% (106 of 112). Intraoperatively, 159 sentinel lymph nodes were detected using a NIR camera, and 165 were detected by using a gamma probe, resulting in a concordance rate of 96.4% (79). Routine use of MSOT in the clinic for diagnosis and management of melanomas will be beneficial (80).…”
Section: Dermatologic Imagingmentioning
confidence: 99%
“…In near-filed applications such as non-melanoma skin cancers MSOT already successfully distinguished skin cancer from normal skin, being helpful for the visualization of lesion margins [13,14]. Even the detection of metastatic spread of melanoma to sentinel lymph nodes appears to be improved with MSOT when compared to current sentinel lymph node excision protocols [25,26]. Further, it was demonstrated that the injection of indocyanine green (ICG) and the detection via MSOT could be a proper replacement strategy for scintigraphy approaches [26].…”
Section: Current Clinical Applicationsmentioning
confidence: 99%